The Relation Between Hiring Queuers and Emotions - A Pre-Study of Experiment Design - Liao, Ruo-Yin; Liang, Chih-Chin (International Journal of Informatics and Information Systems, 2020)
Consumers considering whether or not to queue make their decisions based on queuing size and the expecting waiting time. If a consumer is frustrated because he / she cannot know how long will wait, he / she will quit from a Consumers who are frustrated because they do not know how long they must wait will quit a queue or ask someone for help if the good is worthy to pay more money to own. If a good is worth waiting to purchase, a consumer will chose waiting or buying the privilege to get the good. However, a long wait causes customers to have negative feelings about the queue. Frustration also has a substantial effect on customer loyalty to a good. Therefore, the relationship between perceived waiting time and paying for queuers to buy the good is worth studying. Frustration is a moderating effect that is also worth studying. In the formal study, to make the frustrating emotion, the authors asked all participants to have a contest before they can take the tickets to enter a queue for taking the ticket to a famous concert in Taiwan. The questions used in the contest had different levels of difficulty. However, the difficulty of the questions must be verified before the formal experiment. Therefore, the 60 participants in this pilot study were asked 40 questions in history, mathematics, and Chinese to find the most difficult ten questions and the less difficulty ten questions for the formal test.